Guide for the development of bicycle facilities, 2012. (American Association of State Highway and Transportation Officials, 2012)
"This guide provides information on how to accommodate bicycle travel and operations in most riding environments. It is intended to present sound guidelines that result in facilities that meet the needs of bicyclists and other highway users. Sufficient flexibility is permitted to encourage designs that are sensitive to local context and incorporate the needs of bicyclists, pedestrians, and motorists."--Publisher's website.